-8(x+9)+2=7x-27

Simple and best practice solution for -8(x+9)+2=7x-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(x+9)+2=7x-27 equation:



-8(x+9)+2=7x-27
We move all terms to the left:
-8(x+9)+2-(7x-27)=0
We multiply parentheses
-8x-(7x-27)-72+2=0
We get rid of parentheses
-8x-7x+27-72+2=0
We add all the numbers together, and all the variables
-15x-43=0
We move all terms containing x to the left, all other terms to the right
-15x=43
x=43/-15
x=-2+13/15

See similar equations:

| 575=23(x+16) | | 3(5x+5)=-39+9 | | 1/4/x=0 | | |x-3|+7=2 | | 9(m-857)=900 | | 2x+7(3x-5)=16+4x | | 16(x+14)=912 | | 7x+20=4x+8 | | 12k^2+32k+8=0 | | 135/x=5 | | 3x/2-1=26 | | 3x-1(x+5=20 | | 42=(12+3x)2 | | 3x-6+4x-17=90 | | 17-3+14b=-2b+14 | | x-331/19=22 | | 3(3x-2)=x+7+4x | | x/10+97=117 | | 6x-4=12x+8 | | x/5+209=229 | | 6x+5x−9x−5=7 | | (7x+3)^2-21=0 | | {7x}{8}-3={23}{4} | | 10+7p=3(1+2p) | | 8–2x=22 | | 8y−6=5y+9 | | -1-2x=-5x+20 | | 1-5x+2=-2 | | 6/(5x+3)=0 | | x-833/4=23 | | 850-s=110 | | 2(x-10=60) |

Equations solver categories